Karakteristik Penghuni Neraka: (Suatu Kajian Tahlili Dalam QS al-A’raf/179) - Syarif, Ahmad Syarif; Ghany, Abdul; Haddade, Hasyim; Muhammad Khadary (Program Studi Ilmu Al-Quran dan Tafsir, 2024)
Abstract: This research discusses the characteristics of the inhabitants of hell in QS al-A'raf/7: 179. This verse explains the characteristics or nature of the inhabitants of hell. This research aims to find out the nature of the characteristics of the inhabitants of hell, and what the characteristics are like. the inhabitants of hell, as well as the impact of the characteristics of the inhabitants in QS al-A'raf/7: 179. The research carried out was library research, the approaches used were an interpretive approach and a theological approach. The results of this research are First, the essence of the characteristics of the inhabitants of hell is, that they have hearts but they are not used to understand the verses of the Qur'an, they have eyes but they do not use them to see the power of Allah SWT., they have ears but they do not use them. to listen to the verses of Allah SWT. Second, related to the characteristics of the inhabitants of hell, they are said in the verse to be livestock, even lower than livestock because they do not utilize the five senses that have been given to them. Third, the impact of the characteristics of the inhabitants of hell is that they are said to be livestock, even more misguided than that, and they are negligent about what has been given to them.